2012
DOI: 10.1259/bjr/61619687
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-electrode radiofrequency ablations using Octopus® electrodes in anin vivoporcine liver model

Abstract: Objectives: The objective of this study was to determine the in vivo efficacy of radiofrequency ablation (RFA) in porcine liver using Octopus j electrodes for creating a large coagulation compared with RFA using clustered electrodes. Methods: A total of 39 coagulations were created using a 200-W generator and clustered electrodes or Octopus electrodes during laparotomy in 19 pigs. Radiofrequency was applied to the livers using four protocols: (1) Group A-1, monopolar mode using a clustered electrode (n511); (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 24 publications
0
36
2
Order By: Relevance
“…The measured ablation volume was 25.3 cm radiofrequency electrodes and found that the extent of coagulation necrosis increased from 0.7 to 1.8 cm as the electrode diameter increased from 24 G to 12 G. Our results are also in line with recent studies using separable clustered electrodes, in which 15-G electrodes showed a larger ablation zone than 17-G electrodes under the same conditions. 10,18 In the present study, there was no significant difference in ablation time between the 15-G and the 17-G groups (8.7 6 3.5 min vs 8.4 6 2.5 min; p 5 0.793). This implies that a 15-G electrode can make a similar size ablation zone with shorter ablation time than a 17-G electrode.…”
Section: Discussioncontrasting
confidence: 48%
“…The measured ablation volume was 25.3 cm radiofrequency electrodes and found that the extent of coagulation necrosis increased from 0.7 to 1.8 cm as the electrode diameter increased from 24 G to 12 G. Our results are also in line with recent studies using separable clustered electrodes, in which 15-G electrodes showed a larger ablation zone than 17-G electrodes under the same conditions. 10,18 In the present study, there was no significant difference in ablation time between the 15-G and the 17-G groups (8.7 6 3.5 min vs 8.4 6 2.5 min; p 5 0.793). This implies that a 15-G electrode can make a similar size ablation zone with shorter ablation time than a 17-G electrode.…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, the mean value of the ablated volume using the single 15-G Octopus® electrode method with a 1-cm inter-electrode distance (group B) was 64.11 cm 3 . According to a previous literature report (15), the mean value of the ablated volume using a single 17-G Octopus® electrode was 33.08 cm 3 under the same conditions. Based on these results, we suggest that a 15-G Octopus® electrode may exhibit better performance than that of a 17-G Octopus® electrode under the same conditions.…”
Section: Discussionmentioning
confidence: 62%
“…Basically, the Octopus® electrode is composed of three, cooled-tip electrodes with a 2.5-cm active tip similar to that of a clustered electrode (15). However, the Octopus® electrode differs from the conventional clustered electrode regarding the separability of each individual electrode using a special adaptor which connects the three cables to one piece.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations